Efeito antitumoral in vitro do óleo essencial de Lippia microphylla Cham (Verbenaceae) - Lopes, Ana Luiza de Oliveira (2021)
Cancer is a term that refers to a set of malignant diseases characterized by the uncontrolled proliferation of undifferentiated cells, capable of invasion and metastasis. Several treatment modalities are available, but their effectiveness is often limited by the development of resistance and high toxicity. Products obtained from medicinal plants are an important source of new therapeutic agents. In this context, essential oils are highlighted, which are complex mixtures of volatile substances, described in the literature with a range of biological effects. Lippia microphylla Cham. (Verbenaceae) is an aromatic species whose essential oil extracted from the leaves has reports of larvicidal, antioxidant, antifungal, antimicrobial, cytotoxic and antitumor activity in vivo in a sarcoma 180 model. However, the mechanism of action of this oil in tumor cell lines human beings has not been described so far. Thus, this work aimed to investigate the in vitro antitumor action of the essential oil from L. microphylla leaves (OE-LM). Cytotoxicity was evaluated in human tumor (HCT-116, HeLa, MCF-7, PC-3, MDA-MB231, SK-MEL-28) and non-tumor (HaCaT) cell lines through the reduction assay of MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide). The most sensitive tumor strain to OE-LM was the melanoma strain SK-MEL-28, for which the oil presented an inhibitory concentration 50% (IC50) of 33.38 ± 1.16 µg/mL. In the nontumor HaCaT lineage, the IC50 value was 58.73 ± 1.10 µg/mL. For the standard drug doxorubicin (DOX), IC50 values were 4.0 and 0.28 μM, in SK-MEL-28 and HaCaT cells, respectively. Thus, it was possible to determine the selectivity index (IS), which showed that the OE-LM (IS: 1.75) was more selective for SK-MEL-28 cells than the DOX (IS: 0.07), in relation to action on non-tumor cells HaCaT. To investigate possible in vitro mechanisms of action of OE-LM in cells of the SK-MEL-28 lineage, its effects on the cell cycle, apoptosis induction and production of reactive oxygen species (ROS) at concentrations equivalent to IC50 and o double (33 and 66 μg/ml). In cell cycle analysis, OE-LM induced a significant increase in the sub-G1 peak (p<0.0001), which is indicative of apoptosis. Morphological characteristics of this type of cell death, such as formation of blebs in the membrane and apoptotic bodies, were observed in the analysis by confocal microscopy. In parallel, in the analysis by flow cytometry, a significant increase in the amount of cells labeled with annexin V-FITC (p<0.0001) was observed, which confirms the induction of apoptosis by the oil. In addition, there was a reduction in the production of ROS production, which indicates that the antitumor effect of OE-LM involves an antioxidant action. Therefore, OE-LM has antimelanoma activity in vitro, which suggests its potential as an anticancer agent.